2013
DOI: 10.5539/jsd.v6n8p84
|View full text |Cite
|
Sign up to set email alerts
|

Stock Market Performance and Sustainable Economic Growth in Nigeria: A Bounds Testing Co-integration Approach

Abstract: The study examined the relationship between stock market performance and economic growth in Nigeria. It utilized the bounds testing co-integration procedure also known as autoregressive distributed lag estimation procedure. The empirical model combined key stock market indicators and some traditional macroeconomic variables to estimate the hypothesized relationship in the study. It found that in the long-run, overall output in the Nigerian economy is less sensitive to changes in stock market capitalization as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…According to Okodua and Ewetan (2013), ARDL process starts with ascertaining the significance of lagged variable coefficients in their error correction model (ECM) via associated F-statistics. Pesaran et al (1999) gave a table containing relevant critical figures for several volume of regressors to overcome difficulties connected to non-standardised forms of asymptotic distribution for automatically calculated F-statistics regardless of I(1) or I(0) status.…”
Section: Estimation Techniquementioning
confidence: 99%
“…According to Okodua and Ewetan (2013), ARDL process starts with ascertaining the significance of lagged variable coefficients in their error correction model (ECM) via associated F-statistics. Pesaran et al (1999) gave a table containing relevant critical figures for several volume of regressors to overcome difficulties connected to non-standardised forms of asymptotic distribution for automatically calculated F-statistics regardless of I(1) or I(0) status.…”
Section: Estimation Techniquementioning
confidence: 99%
“…Equally, Okodua & Ewetan (2013) examined the influence of stock market performance and sustainable economic growth in Nigeria using the Autoregressive Distributed Lag estimation technique and the result revealed that economic growth is insignificant to stock market performance. Okoye & Nwisienyi (2013) examined the influence of stock market on economic growth in Nigeria using multiple regression analysis on annual data such as all share index, market value, capitalisation and GDP between 2000 and 2010.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Financial development connotes improvements in the functioning of the financial sector. These include increased access to financial intermediation, greater diversification opportunities, improved information quality, and better incentives for prudent lending and monitoring [4,5,6]. The purpose of this study is to empirically examine the relationship between financial sector reformed and domestic saving mobilization in Nigeria.…”
Section: Original Researchmentioning
confidence: 99%